Clinical outcomes by infusion timing of immune checkpoint inhibitors in patients with advanced non-small cell lung cancer. (March 2023) - Rousseau, Adrien; Tagliamento, Marco; Auclin, Edouard; Aldea, Mihaela; Frelaut, Maxime; Levy, Antonin; Benitez, Jose C.; Naltet, Charles; Lavaud, Pernelle; Botticella, Angela; Grecea, Miruna; Chaput, Nathalie; et al.
Abstract: Background: We aimed to determine whether immune checkpoint inhibitors (ICI) time-of-day infusion might influence the survival of patients with advanced non-small cell lung cancer (NSCLC). Methods: We retrospectively analysed patients who received single-agent anti-PD-(L)1 therapy in any line between 2016 and 2021. We calculated by Cox regression models the association between the proportion of ICI infusions received after 16:30h and overall survival (OS) and progression-free survival (PFS). Results: 180 patients were included, 77% received ICI as second- or further-line (median of 12 infusions/patient). The median age was 65 years (IQR 57–70), 112 patients (62%) were male, 165 (92%) were current or former tobacco smokers, 140 (78%) had performance status (PS) 0 or 1, 26 (14%) were on steroid therapy at ICI initiation. Histology was non-squamous for 139 (77%), the median number of metastatic sites was 3, and 33% had brain metastases. Patients who received at least 20% of ICI infusions after 16:30h (65 out of 180, 36%) had a statistically significant shorter median PFS as compared with patients receiving less than 20% of infusions in the evening (4.9 vs 9.4 months, log-rank p = 0.020), while numerical but not statistical shorter OS was observed (14.0 vs 26.2 months, log-rank p = 0.090). In the multivariate analysis, receiving at least 20% of evening infusions did not significantly increase the risk of death, while PS and line of treatment were significantly correlated with the OS. On the contrary, a proportion of ICI administration after 16:30h ≥20% conferred an HR for the PFS of 1.44 (95% CI: 1.01–2.05, p = 0.043), but this prognostic effect was not found when including in the model the total number of ICI infusions received (HR 1.20, 95% CI: 0.83–1.75, p = 0.329). Conclusion: Time-of-day infusion of ICI may impact the survival of patients with advanced NSCLC. Underlying prognostic characteristics and the number of infusions received could represent conceivable confounding factors, linked to increased variance related to ICI infusion timing. Nonetheless, further studies may unravel chronobiological mechanisms modulating ICI efficacy. Highlights: Does immune checkpoint inhibitors (ICI) time-of-day infusion impact on survival? Retrospective study, advanced NSCLC patients receiving single-agent ICI in any line. Non-significant shorter OS in patients receiving ≥20% ICI infusions in the evening. Significant shorter PFS in patients receiving ≥20% ICI infusion in the evening. Chronobiological mechanisms modulating ICI efficacy should be investigated.